GAMBARAN TENTANG SIKAP GURU TERHADAP BULLYING DI KOTA DEPOK - Andi Andi; Karisma Riskinanti (Universitas Mercu Buana Jakarta, 2018)
Abstract. This study aims to describe how the teacher's attitude towards bullying in Depok City. This research uses quantitative descriptive. The subjects in this study were teachers who teach in the city of Depok. With the sampling technique during the trial try snowball sampling and in research with purposive sampling technique. The number of samples in this study were 180 respondents. The measurement in this study uses the Teacher Attitude scale towards Bullying (Alfonso et.al, 2019) with a Cronbach's Alpha value of 0.905. The data analysis technique uses comparative test and regression test. The results of this study indicate how teachers' attitudes towards bullying tend to be neutral but also found to be positive. The most agreed form of bullying by teachers is the form of threatening and relational. The attitude aspect which has the most dominant contribution to predict the teacher's attitude towards bullying is the affective aspect.